2017
DOI: 10.1002/hed.24916
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of a speech pathology synchronous telepractice service for patients with head and neck cancer

Abstract: The synchronous telepractice service provides cost efficiencies over standard care for providing remote specialist speech pathology head and neck cancer intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 51 publications
3
58
0
2
Order By: Relevance
“…Of particular interest are "Oncoquest" [76,77], "QUICATOUCH" [78] and "ScreenIT" [38]. The integration of technology into HNC care has also allowed novel models of care for the assessment and management of swallowing and nutrition and during and following treatment to connect patients in need of health care, with the specialist services they require [79][80][81][82][83]. Patients with HNC have been found to have high levels of confidence in using technology to drive their health care [84] and high levels of satisfaction when using telehealth in place of standard face-to-face intervention [79,81].…”
Section: Technology In Hnc Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest are "Oncoquest" [76,77], "QUICATOUCH" [78] and "ScreenIT" [38]. The integration of technology into HNC care has also allowed novel models of care for the assessment and management of swallowing and nutrition and during and following treatment to connect patients in need of health care, with the specialist services they require [79][80][81][82][83]. Patients with HNC have been found to have high levels of confidence in using technology to drive their health care [84] and high levels of satisfaction when using telehealth in place of standard face-to-face intervention [79,81].…”
Section: Technology In Hnc Managementmentioning
confidence: 99%
“…Furthermore, for patients in geographically diverse locations, the use of telehealth has proffered economic benefits to individuals and to the health service [79,82,85].…”
Section: Technology In Hnc Managementmentioning
confidence: 99%
“…Telepractice is increasingly used in management of OPSCC to improve access to care and alleviate barriers of distance and cost in health care provision . Studies have demonstrated good feasibility, high patient satisfaction and suitability, service efficiencies and cost savings with the use of telepractice for SLP services in OPSCC. Telepractice has also been successful applied to the delivery of other intensive home‐based therapy regimens outside oncology .…”
Section: Introductionmentioning
confidence: 99%
“…Telepractice allows for consultations between specialists and the clinician working directly with the client, therefore improving client outcomes. Telepractice is cost-efficient by reducing travel costs for both the client and the clinician, hospital stay for medical conditions (e.g., aspiration pneumonia, head and neck cancer, paradoxical vocal cord dys-function), medical tests, and overall medical costs to the health care system (Burns, Kularatna, et al, 2017; Burns, Ward, et al, 2017; Coyle, 2012; Towey, 2012a). Although the benefits of telepractice are obvious in terms of improving access and reducing costs, another benefit of telepractice is the quality of services.…”
mentioning
confidence: 99%
“…The treatment of paradoxical vocal cord dysfunction delivered via telepractice facilitated successful treatment outcomes and a first month cost savings of $2,376.72 (Towey, 2012a). A head-and-neck cancer speech-language pathology specialist program compared standard care (i.e., phone/e-mail support and in-person appointments with a specialist) to telepractice (i.e., online consultation between specialist, treating clinician, and client; Burns, Kularatna, et al, 2017; Burns, Ward, et al, 2017). Results indicated that the number and duration of services were significantly reduced in the telepractice condition and that the client and clinician satisfaction of services was higher in the telepractice condition.…”
mentioning
confidence: 99%